An update on the measurements of the depth of shower maximum made at the Pierre Auger Observatory - Aab, A. (2013)
Data continue to be collected at The Pierre Auger Observatory. The Fluorescence telescopes of thePierre Auger Observatory can be used to measure the depth of shower maximum (Xmax) with high precision (20g/cm2 on average). Thus the measurement of the Xmax distribution is the best way to infer properties of the primarycosmic ray, such as its composition, and even the interaction cross-section for the proton component. During theConference we will present our latest measurements of average Xmax and fluctuations of Xmax as a function ofenergy. In this paper we give a general outline of the Xmax analysis and the improvements made with respect topreviously published results.